Education: Anthropological aspects - Goodman, R (Elsevier, 2015)
The discipliine of anthropology has brought a number of important points to bear on the study of education - a relativistic perspective, a holistic approach, and the ethnographic method. At the same time, the study of education has become increasingly common in anthropological accounts, generally under the headings of the study of ethnicity and nationalism, or cognitive and psychological anthropology. This article examines the development of the anthropological study of education and explores why, despite its apparent importance, it is still looking to establish a secure niche as a subfield of the discipline of anthropology.>